Solid-state, ambient-operation thermally activated delayed fluorescence from flexible, non-toxic gold-nanocluster thin films: towards the development of biocompatible light-emitting devices. (13th July 2016) - Talite, M J A; Lin, H T; Jiang, Z C; Lin, T N; Huang, H Y; Heredia, E; Flores, A; Chao, Y C; Shen, J L; Lin, C A J; Yuan, C T
Abstract: Luminescent gold nanoclusters (AuNCs) with good biocompatibility have gained much attention in bio-photonics. In addition, they also exhibit a unique photo-physical property, namely thermally activated delayed fluorescence (TADF), by which both singlet and triplet excitons can be harvested. The combination of their non-toxic material property and unique TADF behavior makes AuNCs biocompatible nano-emitters for bio-related light-emitting devices. Unfortunately, the TADF emission is quenched when colloidal AuNCs are transferred to solid states under ambient environment. Here, a facile, low-cost and effective method was used to generate efficient and stable TADF emissions from solid AuNCs under ambient environment using polyvinyl alcohol as a solid matrix. To unravel the underlying mechanism, temperature-dependent static and transient photoluminescence measurements were performed and we found that two factors are crucial for solid TADF emission: small energy splitting between singlet and triplet states and the stabilization of the triplet states. Solid TADF films were also deposited on the flexible plastic substrate with patterned structures, thus mitigating the waveguide-mode losses. In addition, we also demonstrated that warm white light can be generated based on a co-doped single emissive layer, consisting of non-toxic, solution-processed TADF AuNCs and fluorescent carbon dots under UV excitation.